Comparative characteristics of chitosan extracted from shrimp and crab shell and its application for clarification of pineapple juice (Journal of the Bangladesh Agricultural University, 2020)
The research has been carried out to compare chitosan extracted from shrimp and crab shell waste and to investigate its effect as a clarifying agent as well as preservative on the pineapple juice. Chitosan has been extracted from shrimp and crab shells by chemical process such as demineralization (2%HCl, 16hr), deproteinization (4% NaOH, 20hr) and deacetylation (60% NaOH, 65°C, 20hr). Yield study showed that crab shells contained more chitosan (20.31%) than shrimp offal (16.29%). Physicochemical properties of chitosan extracted from both sources studied for fat binding capacity (FBC), water binding capacity (WBC), solubility, average molecular weight, ash content, moisture content and degree of deacetylation. The degree of deacetylation and solubility were obtained as 76 and 65% for shrimp shell chitosan and 91 and 70% for crab shell chitosan, respectively. However, WBC and FBC of shrimp and crab shells chitosan were found to be 448 and 265 % and 363 and 212%, respectively. The average molecular weight of shrimp (8.76×105 Da) and crab (5.61×105 Da) chitosan was found to be very close to each other. Chitosan was added to pineapple juice as a clarifying agent at a concentration of 0.2, 0.4 and 0.6g/L. It was observed that shrimp chitosan at a concentration of 0.6g/L was more effective at (28±20°C) than crab chitosan after 90 min of addition.  Statistical analyses revealed that source of chitosan possess significant effect on the perceived sensory characteristics of juices when chitosan has been added at a range from 0.2 to 0.6 g/L of pineapple juice. Chitosan also inhibited the growth of some spoilage bacteria. The analyses showed that increases in chitosan concentration extended the quality of the pineapple juice significantly (0.05) by increasing pH values range, reducing TSS value, reducing enzymatic and non-enzymatic browning and controlling the spoilage during the storage time. This study showed that shrimp chitosan was more effective than crab chitosan as a preservative and clarifier on the quality of pineapple juice.J Bangladesh Agril Univ 18(1): 131–137, 2020https://doi.org/10.5455/JBAU.73490